1981
DOI: 10.1002/cyto.990020311
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric measurement of nuclear DNA content variations as a potential in vivo mutagenicity test

Abstract: Mutagen-induced variations of the cellular DNA content have been studied in mouse bone marrow cells in uiuo using high resolution flow cytometric techniques. During the first days after a single injection of the chemical mutagen cyclophosphamide an increased coefficient of variation in the GI peak of the flow histograms was observed. The magnitude and duration of this effect were dose-dependent. The reproducibility of the measurements was high, indicating that individual variability between animals and instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(74 citation statements)
references
References 6 publications
0
73
0
1
Order By: Relevance
“…Following the chopping method of Galbraith et al [21], about 25 mg fresh leaves (dry fruits in case of Euphorbia amygdaloides) from each plant sample were cochopped in Otto's buffer I (Otto et al [22]) together with Pisum sativum (1C = 4.42 pg DNA; Greilhuber and Ebert [23]), Zea mays (1C = 2.73 pg DNA; Doležel et al [24]), Secale cereale (1C = 7.79 pg DNA; Doležel et al [24]), or Solanum pseudocapsicum (1C = 1.29 pg DNA; Temsch et al [25]) as the internal standard organisms. The resulting isolated nuclei were filtered through a 30 µm mesh and subsequently incubated with RNase A for 30 minutes at 37…”
Section: Flow Cytometry (Fcm)mentioning
confidence: 99%
See 1 more Smart Citation
“…Following the chopping method of Galbraith et al [21], about 25 mg fresh leaves (dry fruits in case of Euphorbia amygdaloides) from each plant sample were cochopped in Otto's buffer I (Otto et al [22]) together with Pisum sativum (1C = 4.42 pg DNA; Greilhuber and Ebert [23]), Zea mays (1C = 2.73 pg DNA; Doležel et al [24]), Secale cereale (1C = 7.79 pg DNA; Doležel et al [24]), or Solanum pseudocapsicum (1C = 1.29 pg DNA; Temsch et al [25]) as the internal standard organisms. The resulting isolated nuclei were filtered through a 30 µm mesh and subsequently incubated with RNase A for 30 minutes at 37…”
Section: Flow Cytometry (Fcm)mentioning
confidence: 99%
“…The nuclei were then stained in Otto's buffer II (Otto et al [22]) containing the fluorochrome propidium iodide (PI, 50 µg/ml) for 1 hour or overnight in the refrigerator. For measurement, a CyFlow ML flow cytometer or a PAII (both Partec, Muenster, Germany) was used.…”
Section: Flow Cytometry (Fcm)mentioning
confidence: 99%
“…Propidium iodide, the fluorochrome used in flow cytometry analysis, intercalates into double-stranded DNA without base-dependent bias, making it suitable for estimating DNA amount (Dolezel et al, 2007). High heterogeneity in DNA amount suggests a lower quality of adipocyte nuclei because it represents higher dispersion in the DNA amount, which may be because of structural and numerical chromosomal aberrations as well as the formation of micronuclei (Otto et al, 1981). It was previously shown that treatment with a mutagen drug increased the CV in a dose-dependent manner, as measured by flow cytometry (Otto et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, flow cytometry was shown to be a highly sensitive procedure to detect the effects of mutagens on DNA content both in vivo (15) and in vitro using intact nuclei (7) and isolated chromosomes (14). The advantages of flow cytometry over other cytological techniques applicable to mammalian tissues include the rapidity with which the test can be performed, the large number of cells that can be counted, and the potential diversity of tissues that can be analysed (1,5).…”
mentioning
confidence: 99%